AGRICULTURE LENDING FROM THE BANKING SECTOR (ALBANIA CASE) - Eneida Thomaj (European Scientific Journal, ESJ, 2014)
Agriculture is one of the main sectors in Albanian economy, were most of rural population is engaged in (according to 2013 official data, 52% of total employees is engaged in agriculture). Regardless of this, agriculture contribution to domestic GDP is around 18.9% (according to 2012 official data). There are 16 banks operating in Albanian financial market, which dedicate to agriculture no more than 2-5% of their lending portfolio, mainly because of creditworthiness of farm units. Lack of agriculture lending constitutes a limiting factor for agriculture development. As such, in our study we tried to find solutions on how to increase farm units’ creditworthiness, firstly by understanding the banks perception on agriculture lending. A survey, among 10 banks in Albania was made, to identify factors which might be taken in consideration when analyzing agriculture lending expansion (such as future expectations for agriculture lending, performance of loan portfolio). Secondly, a linear regression model was build which links the seasonality of agricultural products prices with loans granted to agriculture. While the model showed some positive results, variables used are selected in terms of limited quantitative data and short time series. The goal of this paper is to contribute to discussion of the possible ways of increasing agriculture lending from banking sector through the seasonality of agriculture products prices, based on the actual conditions of farm unit, by providing a comprehensive overview of the performance of banking sector in Albania.